ACMR/I System - Parker, J. (International Foundation for Telemetering, 1977)
International Telemetering Conference Proceedings / October 18-20, 1977 / Hyatt House Hotel, Los Angeles, California === The instrumentation system described provides real-time attitude and position data on 8 high-dynamic fighter aircraft and position data on 12 additional cooperative targets. Position data is derived from multilateration range measurements using FM-CW phasecomparison techniques. Attitude and acceleration data is obtained from a strap-down inertial system initialized by the ranging system. Digital data is transmitted to and from the target by frequency shift keying of the ranging carrier. A multiprocessor ground computer using Kalman filter techniques provides a total state vector for each participant at a rate of 10 per second. The multiprocessor also provides real-time missile simulation for performance scoring. The Display and Debriefing Subsystem provides real-time computer-drawn pseudo three-dimensional display of the aircraft, total replay capability, and control of the entire system from the operator's console.